Application Of Make A Match Type Of Cooperative Learning Model To Increase Learning Activity Of Class V Students 0308 State Elementary School Aek Borgot - Ahmad Sapri Nasution; Hasrijal Hasrijal; Nauli Tama Sari (Indonesian Journal of Basic Education, 2022)
The purpose of this research is to increase the learning activity of fifth grade students of SD Negeri 0308 Aek Borgot using the make a match type of cooperative learning model for the 2020/2021 school year. The learning activities referred to in this study include physical and mental activities. This type of research is classroom action research (CAR), where the teacher is the executor of learning and the researcher is the observer. The object of research is student learning activity. Data collection techniques using observation and interviews. Data were analyzed descriptively and presented in the form of tables and graphs. The results showed an increase in student learning activities, namely 73.53% (good category) in the first cycle, then increased to 85.29% (very good category) in the second cycle. This means that there is an increase of 11.76%. Therefore, the use of the matching type cooperative learning model in social studies subjects can increase the learning activities of fifth graders at SD Negeri 0308 Aek Borgot